A trilogia zambeziana de Gavicho de Lacerda: O alvorecer da literatura colonial portuguesa - Helder Maia (Moderna Språk)
The Zambezian trilogy, by Gavicho de Lacerda, published in the 1920s, is part of the dawn of Portuguese colonial literature with a Mozambican theme. However, the works didn’t achieve public acclaim through the Concursos de Literatura Colonial, nor are they part of the corpus of recent publication on colonial literature with a Mozambican theme (Noa, 2002; Sousa, 2013), except for the thesis by Neves (2016). In this article, from the analysis of the books Cartas da Zambézia (1920), Costumes e Lendas da Zambézia (1925) and Figuras e Episódios da Zambézia (1929), we seek to understand how the author constructs miscegenation and the relations between colonizers and colonized, just as we seek to infer gender and sexuality perspectives on African populations, especially non-assimilated ones.